Bidirectional associations and developmental trajectories between physical activity and weight self‐stigma among adolescents with high body weight/obesity: A longitudinal study - Kanglin Wang; Zaihao Wu; Jian Sun; Changkun Tang; Fen Qiu (Applied Psychology: Health and Well-Being, 2026)
Abstract Adolescents with overweight/obesity face co‐occurring declines in physical activity (PA) and intensifying weight self‐stigma (WSS), yet the longitudinal reciprocal dynamics remain poorly understood, particularly outside Western contexts. This three‐wave study examined developmental trajectories and within‐person bidirectional associations between PA and WSS in 325 Chinese adolescents ( M age = 15.41), using latent growth curve and random‐intercept cross‐lagged panel models to disentangle stable between‐person differences from temporal fluctuations. PA showed a significant linear decrease ( β = −.25) while WSS linearly increased ( β = .31). Parallel growth analyses revealed that higher initial PA predicted slower WSS accumulation ( β = −.22), and higher initial WSS forecasted steeper PA declines ( β = −.20). Critically, reciprocal within‐person effects emerged only during the academic semester (T1 → T2): deviations above one's typical PA level reduced subsequent WSS ( β = −.15), and elevated WSS suppressed later PA ( β = −.18), whereas the corresponding cross‐lagged effects were not significant during the winter vacation (T2 → T3), underscoring context‐dependent temporality. No gender moderation was detected. These findings demonstrate that PA and WSS form a mutually reinforcing loop that is acutely sensitive to environmental structure, informing targeted, phase‐sensitive interventions that combine stigma reduction with PA promotion within naturalistic educational settings.